2015
DOI: 10.1038/nsmb.3129
|View full text |Cite
|
Sign up to set email alerts
|

Structure of full-length human anti-PD1 therapeutic IgG4 antibody pembrolizumab

Abstract: Immunoglobulin G4 antibodies exhibit unusual properties with important biological consequences. We report the structure of the human full-length IgG4 S228P anti-PD1 antibody pembrolizumab, solved to 2.3-Å resolution. Pembrolizumab is a compact molecule, consistent with the presence of a short hinge region. The Fc domain is glycosylated at the CH2 domain on both chains, but one CH2 domain is rotated 120° with respect to the conformation observed in all reported structures to date, and its glycan chain faces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
175
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(183 citation statements)
references
References 39 publications
5
175
0
3
Order By: Relevance
“…However, in these chains, both loop conformations are involved in crystal packing interactions (with an average area of ∼147 Å 2 ). More recently, a crystal structure of intact IgG4, solved under cryogenic conditions, revealed an IgG1-like Cγ2 FG loop conformation in one chain, in the absence of crystal packing interactions (Scapin et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in these chains, both loop conformations are involved in crystal packing interactions (with an average area of ∼147 Å 2 ). More recently, a crystal structure of intact IgG4, solved under cryogenic conditions, revealed an IgG1-like Cγ2 FG loop conformation in one chain, in the absence of crystal packing interactions (Scapin et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…The recent crystal structure of intact IgG4 (Scapin et al, 2015) revealed an unusual position for one of the Cγ2 domains, which was rotated by ∼120°, exposing the carbohydrate moiety covalently attached to Asn297. In the FG loop from this domain, torsion angles for Lys326 (ψ) (103°), Gly327 (φ) (132°) and Ser331 (φ) (−133°) are comparable to the range of torsion angle values for the unique IgG4-like conformation in the cryogenic and RT IgG4-Fc structures [Lys326 (ψ), 102 to 125°; Gly327 (φ) 77 to 128°; Ser331(φ), −143 to −160°], which differ from the range of typical torsion angle values found in high resolution IgG1-Fc structures [Lys326 (ψ), −3 to −41°; Ala327 (φ), −66 to −103°; Pro331 (φ), −41 to −71°].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 plots the 498 human Fab and four mammalian mAb crystal structures in the PDB database by resolution [9], release date from the PDB, and technical application. The symbol, “Y”, marks the publication of four intact mammalian IgG structures (1HzH, 1IGT, 1IGY, and 5DK3) [3235]. Solid squares represent the 164 apo-Fabs (Fabs with no bound antigen).…”
Section: Discussionmentioning
confidence: 99%
“…19 Unlike other immunoglobulin G subclasses (IgG1, IgG2 and IgG3), the IgG4 isotype has a low affinity for C1q and Fc receptors which allows pembrolizumab to bind to PD-1 on T cells without activating the complement system. 20 Thus, pembrolizumab is capable of blocking the PD-1/PD-L1 interaction while simultaneously preserving the host T-cell antitumor functions.…”
Section: Introduction To Pembrolizumabmentioning
confidence: 99%